Dahsyatul Maut Fī Syi’r ‘Ḥub’ Li Adūnīs (The Astonishment of Death in Hubb Poetry by Adonis) - Hamidah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2018)
Ahmed Said Asbar (Adonis) was one of the Syrian poets who invented the world’s free poetry Arabic literature. Hubb from the Adonis Library on the theme “First Poems” in the section “Songs to Death” contains simple words and rich meaning and romantic words. The poet pictures love at the first and then sealed with the question of death. The researcher found that finding the meaning in this poetry needs the appropriate analytical method and the most appropriate for the analysis is the method of the semiotic analysis of Michael Riffatere. In this research, the researcher used a semiotic analysis, which was invented by Michael Riffatere. In this analysis, there are three steps: (1) reading poetry, heuristic and hermeneutic; (2) defining the subject by finding the matrix, model, and varians; (3) creating a hypogram or comparing the text of Hubb and the other text. The researcher found that after the reading of the poetry, the sociological criterion in the Hubb of Adonis was death and astonishment. In order to achieve this criterion, the researcher found that the model used is the last part of the text and the text that became the hypogram of Hubb is from one of the poems by Mahmud Sami Pasha al-Baroudi.